2022
DOI: 10.3389/fcell.2022.893546
|View full text |Cite
|
Sign up to set email alerts
|

A Novel DNA Repair Gene Signature for Immune Checkpoint Inhibitor-Based Therapy in Gastric Cancer

Abstract: Gastric cancer is a heterogeneous group of diseases with only a fraction of patients responding to immunotherapy. The relationships between tumor DNA damage response, patient immune system and immunotherapy have recently attracted attention. Accumulating evidence suggests that DNA repair landscape is a significant factor in driving response to immune checkpoint blockade (ICB) therapy. In this study, to explore new prognostic and predictive biomarkers for gastric cancer patients who are sensitive and responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…Our study found that compared with the high DDR group, the low DDR group had stronger immune cell infiltration, with immunosuppressive cells such as NK cells and M2 macrophages enriched in the high DDR group, leading to poorer prognosis, while the activated T cells and B cells were more abundant in the low DDR group, resulting in a better prognosis. Moreover, in gastric cancer and melanoma, it has also been found that patients with low DDR scores have significantly increased immune infiltration, consistent with our results ( 43 , 44 ). Studies have shown that changes in tumor DDR pathways are significantly correlated with the response to immune checkpoint inhibitors (ICIs) and can also affect patient survival ( 45 48 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that compared with the high DDR group, the low DDR group had stronger immune cell infiltration, with immunosuppressive cells such as NK cells and M2 macrophages enriched in the high DDR group, leading to poorer prognosis, while the activated T cells and B cells were more abundant in the low DDR group, resulting in a better prognosis. Moreover, in gastric cancer and melanoma, it has also been found that patients with low DDR scores have significantly increased immune infiltration, consistent with our results ( 43 , 44 ). Studies have shown that changes in tumor DDR pathways are significantly correlated with the response to immune checkpoint inhibitors (ICIs) and can also affect patient survival ( 45 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…significantly increased immune infiltration, consistent with our results (43,44). Studies have shown that changes in tumor DDR pathways are significantly correlated with the response to immune checkpoint inhibitors (ICIs) and can also affect patient survival (45-48).…”
Section: Discussionsupporting
confidence: 91%
“…In several cancers, various GES have been found to be capable of predicting ICI response, including in melanoma [ 115 117 ], NSCLC [ 118 121 ], gastric cancer [ 122 ], lower-grade glioma [ 123 ] and some across multiple cancer types such as in both NSCLC and melanoma [ 124 ]. In addition, a pan-tumor signature predictive of ICI response was derived from 220 patients across HNSCC, gastric cancer, triple-negative breast cancer, bladder, anal canal, biliary, colorectal, esophageal, and ovarian cancers.…”
Section: Exploratory Biomarkers For Immune Checkpoint Inhibition In S...mentioning
confidence: 99%
“…For example, as recent evidence revealed, DNA repair landscape is a significant factor in driving response to immune checkpoint blockade therapy (27). We developed a novel 15-DNA repair gene signature (DRGS) and scoring system to evaluate its efficiency in discriminating different molecular and immune characteristics and therapeutic outcomes of patients with gastric cancer (28). Multi-omics data analysis demonstrated that the patients with high DRGS score were characteristic of high levels of anti-tumor lymphocytes infiltration, tumor mutation burden (TMB) and PD-L1 expression, and such patients exhibited a longer overall survival and may benefit more from immune checkpoint blockade therapy, as compared to the low-score patients (28).…”
Section: Prognostic/predictive Multigene Expression Signature Develop...mentioning
confidence: 99%